The Castaway Effect of Obesity; The Need For Implication Is Now! - Madhani Sarosh; Sadia Fatima Syeda (Journal of Obesity Management, 2016)
Apart from the physical health implications obesity partakes on an individual; it also takes its toll on mental and psychological wellbeing of a person. A vicious cycle starts with hostility based on ‘obesity stigma’, eventually leading the person being stuck in a positive feedback loop. Every attempt to correct his or her obesity problem results in severe detrimental health effects. It is necessary that appropriate awareness programs and legislations are drafted and implemented to strike out the root causes of obesity stigma.
Keywords: Obesity